2020
DOI: 10.12964/jsst.20005
|View full text |Cite
|
Sign up to set email alerts
|

Symbolism of Snakes that Stimulate Restoration and Transformation of Visceral Vitality

Abstract: Snakes are animals that often appear in religion, mythology, and fairytales. In these stories they have both sacred and destructive qualities. Snakes also appear as powerful emotions in individual dreams and sandplay cases. These snakes appear when consciousness is quite separated from instinct and provide an individual with a crucial opportunity for development and regression. Therefore, this study amplified various symbols of snakes and examined their meanings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…She also expressed the helplessness she felt in the relationship with her own children through the appearance of the tiger. However, from a deeper perspective, the client met a snake, a symbol of feminine wisdom and libido vitality (Kim, 2020) in the sandbox, and a seashell, a symbol of spiritual archetypes, and the possibility of new development (Carey, 1999), that showed that her fragile ego was experiencing new developmental possibilities. Based on these intense experiences, the client first spoke of the uncomfortable feelings she felt toward the analyst, who was mainly silent during previous sessions.…”
Section: Picture 1 I Am Playingmentioning
confidence: 99%
“…She also expressed the helplessness she felt in the relationship with her own children through the appearance of the tiger. However, from a deeper perspective, the client met a snake, a symbol of feminine wisdom and libido vitality (Kim, 2020) in the sandbox, and a seashell, a symbol of spiritual archetypes, and the possibility of new development (Carey, 1999), that showed that her fragile ego was experiencing new developmental possibilities. Based on these intense experiences, the client first spoke of the uncomfortable feelings she felt toward the analyst, who was mainly silent during previous sessions.…”
Section: Picture 1 I Am Playingmentioning
confidence: 99%